Spray Preparation Nanoemulsion Containing Butterfly Pea Flower (Clitoria ternatea L) Ethanol Extract as an Antiaging Nanocosmetic - Yuniarti, Lelly; Bhatara, Tryando; Tejasari, Maya; Dewi, Miranti Kania; Ahmad, Sadiah; Kharisma, Yuktian (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background:  Nanotechnology has the potential to produce innovations in drug formulation and drug delivery systems. Nanocosmetics and nanocosmeceuticals containing natural ingredients have been proven to overcome the weaknesses of traditional cosmetics and also add value to their formulations.Objective: This study aims to analyze the application of nanocosmeceutical technology based on ethanol extract of butterfly pea flower (Clitoria Ternatea L) in the preparation of nanoemulsion spray as a skin antiaging agent for the growth of collagen, elastin and extracellular matrix.Methods Method used true experimental design with posttest control group with random allocation to model mice given UVB radiation. The levels of collagen, elastin, and cellular matrix extract were assessed using Verhoef staining and observed by two experts,Results: The results of this research show that a nanoemulsion spray preparation of ethanol extract of butterfly pea flower (Clitoria Ternatea L) improves skin damage in aging model mice by increasing the production of extra cellular matrix, collagen and elastin. Conclusion: The preparation of butterfly pea flower flower extract nanoemulsion sprey (Clitoria Ternate L) has antiaging, collagen and elastin formation activities